Understanding and analysing competency based curriculum in pharmacology for developing syllabus and teaching schedules - Khilnani, Gurudas; Khilnani, Ajeet Kumar; Thaddanee, Rekha (International Journal of Basic & Clinical Pharmacology, 2020)
The competency based curriculum has already been implemented in phase-I (1st professional MBBS) and medical institutes, through curriculum committees, are gearing up for designing and developing curricular contents for phase-II training beginning from October, 2020. We have analysed curricular components as given in CBME documents with respect to distribution of contents and time allotted for cognitive and skill training and assessment. The objectives of this analysis are to understand distinctive features, identify elements required for organization of teaching sessions and facilitate preparation of teaching schedules. We segregated competencies according to corresponding system and domain of learning to distribute teaching hours. It was observed that 64 competencies in cognitive domain shall be covered in 80 hours assigned for lectures. The new curriculum has given importance to clinically relevant topics such as drug regulations, pharmaco-economics, pharmacology of eye and skin disorders, vaccines, national health programs (would require integration), environmental pollutants, food adulterants, stings and bites, and pharmacological considerations in geriatric and paediatric therapy. Ironically, antimicrobial agents and anti-fungals do not appear in the document as separate competencies. The 138 non-lecture hours can be divided into small group discussions (seminars) and tutorials for 19 hours each and remaining 100 hours can be reserved for practicals (skill training). About 27% of time assigned for practical training shall be required for developing proficiency for certification in 4 competencies and 25 competencies in cognitive domain shall require integration. Finally, steps are described to construct subject specific sessions giving one example each for a non-integrated and an integrated session.